X‐ray speckle visibility spectroscopy in the single‐photon limit. (8th February 2013) - DeCaro, Curt; Karunaratne, Vidanage Nuwan; Bera, Sambhunath; Lurio, Laurence B.; Sandy, Alec R.; Narayanan, Suresh; Sutton, Mark; Winans, John; Duffin, Kirk; Lehuta, Jon; Karonis, Nicholas
<x xml:space="preserve">Abstract</x> The technique of speckle visibility spectroscopy has been employed for the measurement of dynamics using coherent X‐ray scattering. It is shown that the X‐ray contrast within a single exposure can be related to the relaxation time of the intermediate scattering function, and this methodology is applied to the diffusion of 72 nm‐radius latex spheres in glycerol. Data were collected with exposure times as short as 2 ms by employing a resonant shutter. The weak scattering present for short exposures necessitated an analysis formalism based on the spatial correlation function of individual photon charge droplets on an area detector, rather than the usual methods employed for intensity correlations. It is demonstrated that this method gives good agreement between theory and experiment and thus holds promise for extending area‐detector‐based coherent scattering methods to the study of faster dynamics than previously obtainable.